2013
DOI: 10.1371/journal.pone.0052996
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Mitochondrial Proteins HSP60 and ATP Synthase from Ascidian Eggs: Implications for Antibody Specificity

Abstract: Use of antibodies is a cornerstone of biological studies and it is important to identify the recognized protein with certainty. Generally an antibody is considered specific if it labels a single band of the expected size in the tissue of interest, or has a strong affinity for the antigen produced in a heterologous system. The identity of the antibody target protein is rarely confirmed by purification and sequencing, however in many cases this may be necessary. In this study we sought to characterize the myopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…; Chenevert et al . ). Interestingly, exomitochondrial F 1 ‐ATPase subunits have been proven to bind to some cytoskeletal filaments and myoplasmin‐C1 (Nishikata & Wada ) and are thought to form a novel complex without F 0 subunits.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Chenevert et al . ). Interestingly, exomitochondrial F 1 ‐ATPase subunits have been proven to bind to some cytoskeletal filaments and myoplasmin‐C1 (Nishikata & Wada ) and are thought to form a novel complex without F 0 subunits.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we revealed that the aand b-subunits of F 1 -ATPase are exomitochondrially localized to the cortical region of the myoplasm in the ascidian egg (Ishii et al 2012;Chenevert et al 2013). Interestingly, exomitochondrial F 1 -ATPase subunits have been proven to bind to some cytoskeletal filaments and myoplasmin-C1 (Nishikata & Wada 1996) and are thought to form a novel complex without F 0 subunits.…”
Section: Target Molecules Of Nan 3 Involved In Cytoplasmic and Corticmentioning
confidence: 98%
See 2 more Smart Citations
“…Membranes were incubated in 2% milk with anti-Mad1 antibody (1:3000) or anti-Mad2 antibody (1:1000), then washed and incubated with anti-mouse horseradish peroxidase-conjugated secondary antibody (Jackson ImmunoResearch, 1:10,000). The blots were subsequently reprobed with anti-tubulin DM1A (Sigma-Aldrich, 1:3000, mouse) or anti-ATP synthase NN18 [22] (Sigma-Aldrich, 1:5000, mouse) as loading controls.…”
Section: Western Blot Analysismentioning
confidence: 99%